Metode Sabak, Sabki, Manzil di Ma’had ‘Aly Imam Bukhari Putri - Munzillah, Indiarti Muafiqoh; Hanani, Hanif (Lembaga Yasin AlSys, 2024)
The Islamic Religious Education (PAI) curriculum is a curriculum that needs to be emphasized on the process and results, where students learn it and then apply or apply it in their daily lives, both for the school environment, family, or for themselves. Education is an important thing for every individual, especially religious science education which is knowledge in understanding Islam, as a guide and guideline for life in the world. One way to understand Islam is to study the Qur'an and memorize it. Memorization is a process that requires time, perseverance, and patience. Memorization cannot be done instantly, except for servants who Allah has given ease in memorizing the Qur'an. This research has the objectives of 1) to find out the method of sabak, sabki, manzil in memorizing the Qur'an, and 2) to find out the implementation of the sabak, sabki, manzil and aisar methods in Ma'had 'Aly Imam Bukhari Putri. This type of research is field research with qualitative research methods. The results of the research, namely the sabak, sabki, and manzil methods, are curriculum development that has its own innovations and characteristics. The sabak, sabki, and manzil methods focus more on adding and improving the memorization of female students. Even so, the memorization and reading of female students are corrected, especially in the science of tajweed while the aisar method for female students who have readings that need to be improved from the basics.